The nature and determination of the dynamic glass transition temperature in polymeric liquids - Mlynarczyk, Paul John (Kansas State University, 2014)
A polymer has drastically different physical properties above versus below some characteristic temperature. For this reason, the precise identification of this glass transition temperature, T[subscript]g, is critical in evaluating product feasibility for a given application. The objective of this report is to review the behavior of polymers near their T[subscript]g and assess the capability of predicting T[subscript]g using theoretical and empirical models. It was determined that all polymers begin to undergo structural relaxation at various temperatures both nearly above and below T[subscript]g, and that practical assessment of a single consistent T[subscript]g is successfully performed through consideration of only immediate thermal history and thermodynamic properties. It was found that the best quantitative structure-property relationship (QSPR) models accurately predict T[subscript]g of polymers of theoretically infinite chain length with an average error of less than 20 K or about 6%, while T[subscript]g prediction for shorter polymers must be done by supplementing these T[subscript]g (∞) values with configurational entropy or molecular weight relational models. These latter models were found to be reliable only for polymers of molecular weight greater than about 2,000 g/mol and possessing a T[subscript]g (∞) of less than about 400 K.
Keywords: Structural relaxation; Polymer science; Glass transition temperature; Quantitative structure-property relationship; Chemical Engineering (0542); Polymer Chemistry (0495)